An investigation of project-based learning and computer simulations to promote conceptual understanding in eighth grade mathematics - Sylvester, Allen (Kansas State University, 2007)
The goal of this study was to explore the use of interdisciplinary PBL projects for teaching mathematical concepts according to NCTM (2000) goals for mathematics instruction. This study sought to answer the question: what are the teaching issues and evidence of student learning of mathematical concepts over a series of three interdisciplinary PBL projects involving STELLA™ modeling software which are designed to engage students, integrate technology, and provide a context for learning mathematics based on the 5 NCTM (2000) goals? HyperStudio™ was used as a communication tool with which students built artifacts of understanding. This study was a naturalistic case study employing videotaped observations, interviews, student-peer reviews and student generated artifacts of learning as data sources. Data were categorized into two variable clusters: Teaching and Learning. Implementation issues for three computer-based PBL simulations are discussed. Themes that emerged from analysis of the data are grouped into teaching themes and learning themes. Themes relating to teaching include the struggle to form a community of learners, relevancy of the simulations to middle school students, need for group-worthy projects, helping students balance creativity and content, lesson adaptation, and critical review and student reflection on constructive feedback. Findings of the study suggest the students were able to meet a majority of the expected content goals. Themes relating to learning include the struggle to find a balance between creativity and content, ownership and control, engagement with the simulations, and students’ ability to think and express themselves mathematically. Recommendations are made for teachers who wish to implement PBL, simulations, and similar teaching strategies and for researchers who are studying similar learning environments.
Keywords: Projects; Learning; Standards; Computers; Teaching methods; Simulations; Education, Mathematics (0280); Education, Secondary (0533); Education, Technology (0710)